Relative Biological Effectiveness (RBE) of (131)I Radiation Relative to (60)Co Gamma Rays - Neshasteh-Riz, Ali (Royan Institute, 2013)
OBJECTIVE: To assess relative biological effectiveness (RBE) of (131)I radiation relative to (60)Co gamma rays in glioblastoma spheroid cells. MATERIALS AND METHODS: : In this experimental study, glioblastoma spheroid cells were exposed to (131)I radiation and (60)Co gamma rays. Radiation induced DNA damage was evaluated by alkaline comet assay. Samples of spheroid cells were treated by radiation from (131)I for four different periods of time to find the dose-response equation. Spheroid cells were also exposed by 200 cGy of (60)Co gamma rays as reference radiation to induce DNA damage as endpoint. RESULTS: Resulted RBE of (131)I radiation relative to (60)Co gamma rays in 100 µm giloblastoma spheroid cells was equal to 1.16. CONCLUSION: The finding of this study suggests that (131)I photons and electrons can be more effective than (60)Co gamma rays to produce DNA damage in glioblastoma spheroid cells.